Strategie dyskursu i zabiegi perswazyjne w artykułach na temat szczepień na portalu Onet.pl - Nowakowska, Magdalena (Acta Universitatis Lodziensis. Folia Linguistica, 2018)
The aim of the article is to present the strategies regulating discourse concerned with the topic of vaccinations in press releases published on the Onet.pl website in the 2017. The authors of the materials posted on this popular website implement a number of strategies based on discretization and the refusal to allow those against vaccinations to expose their views. With respect to particular strategies one may also find popular techniques of social influence or the use of the rhetoric of fear, guilt, and shame which is concerned with persuasive aims. The message is cohesive and coherent, critical towards the voices opposing the reasonableness of vaccinations.